2009
DOI: 10.4088/pcc.08m00724
|View full text |Cite
|
Sign up to set email alerts
|

Time-Invariant and Time-Varying Predictors of Depression Symptoms in Primary Care Patients

Abstract: Objective: The aims of this study were to examine correlates of depression symptoms, baseline predictors of change in depression symptoms, and time-varying predictors of depression symptoms in a primary care sample.Method: In this study, we assessed depression symptoms and other variables at 3 time points over the course of 6 months in 103 primary care patients with elevated depression symptoms at baseline. Data collection occurred from May 2004 to September 2007.Results: Individuals with lower income levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Certainly, the presence of chronic pain in the general population is associated with increased levels of depression , and within samples of people with chronic pain, pain severity, and depression symptom severity are correlated . In fact, as severity of pain fluctuates in individuals over time, so does level of depressive symptoms . Previous research specifically in HIV‐infected populations has documented that the presence of pain in the past week is associated with more anxiety and depression symptoms , having a psychiatric illness , and generally poorer mental and physical health .…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the presence of chronic pain in the general population is associated with increased levels of depression , and within samples of people with chronic pain, pain severity, and depression symptom severity are correlated . In fact, as severity of pain fluctuates in individuals over time, so does level of depressive symptoms . Previous research specifically in HIV‐infected populations has documented that the presence of pain in the past week is associated with more anxiety and depression symptoms , having a psychiatric illness , and generally poorer mental and physical health .…”
Section: Introductionmentioning
confidence: 99%
“…These differences suggested that the association between chronic pain intensity and depression needs to be further explored. For an individual, the severity of pain varies over time as does the degree of depressive symptoms (Uebelacker et al, 2009). This may provide a plausible explanation for the lack of a significant relationship between depression and chronic pain severity in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We first examined the relationship between students’ academic self-efficacy and their academic-related boredom during three high school years. Students’ academic self-efficacy was treated as a time-varying predictor of their academic-related boredom (Roskam & Meunier, 2012; Uebelacker, Weisberg, Strong, Smith, & Miller, 2009). The model was as follows: academic-related boredom = µ + r 1 (academic self-efficacy) + r 2 (time) + r 3 (academic self-efficacy) × (time) + e. The time metric was 0 (Grade 10), 1 (Grade 11), and 2 (Grade 12).…”
Section: Methodsmentioning
confidence: 99%